'Endurance Work': Embodiment and the Mind–Body Nexus in the Physical Culture of High-Altitude Mountaineering. (December 2018) - Allen-Collinson, Jacquelyn; Crust, Lee; Swann, Christian
The 2015 Nepal earthquake and avalanche on Mount Everest generated one of the deadliest mountaineering disasters in modern times, bringing to media attention the physical-cultural world of high-altitude climbing. Contributing to the current sociological concern with embodiment, here we investigate the lived experience and social 'production' of endurance in this sociologically under-researched physical-cultural world. Via a phenomenological-sociological framework, we analyse endurance as cognitively, corporeally and interactionally lived and communicated, in the form of 'endurance work'. Data emanate from in-depth interviews with 18 high-altitude mountaineers, 10 of whom experienced the 2015 avalanche. The article responds to Shilling's call to address an important lacuna identified in sociological work: the need to investigate the embodied importance of cognition in the incorporation of culture. The concept of endurance work provides a powerful exemplar of this cognitive–corporeal nexus at work as a physical-culturally shaped, embodied practice and mode-of-thinking in the social world of high-altitude climbing.